PERAN SISTEM INFORMASI MANAGEMENT (SIM) DALAM PENGAMBILAN KEPUTUSAN - Sinta Dewi Octavia Sakti; Dwihanus Dwihanus (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
In keeping with the times today that in the management of human resources ef ectively, every organization is absolutely necessary to create a human resources information system for the development of information systems could affect decision-making in an institution. Expected decision- making is a process towards better so with pegetahuan accruing from the information system will add to the discourse, consideration and finally decided appropriately. For information system consists of components supporting educational institutions to provide information needed by decision-makers when making educational activities